Respuesta :
Given function: f(x) = (3x+5)/7
y = f(x) so it's the same as y = (3x+5)/7
Swap every copy of x and y to get x = (3y+5)/7
Solve for y to get....
x = (3y+5)/7
7x = 7*(3y+5)/7
7x = 3y+5
7x-5 = 3y+5-5
7x-5 = 3y
3y = 7x-5
3y/3 = (7x-5)/3
y = (7x-5)/3
So the inverse function is f^(-1)(x) = (7x-5)/3
Answer is choice A
y = f(x) so it's the same as y = (3x+5)/7
Swap every copy of x and y to get x = (3y+5)/7
Solve for y to get....
x = (3y+5)/7
7x = 7*(3y+5)/7
7x = 3y+5
7x-5 = 3y+5-5
7x-5 = 3y
3y = 7x-5
3y/3 = (7x-5)/3
y = (7x-5)/3
So the inverse function is f^(-1)(x) = (7x-5)/3
Answer is choice A
Answer:
Option A. f−1(x) = The quantity of seven x minus five, over three
Step-by-step explanation:
we know that
The given function is equal to
[tex]f(x) = (3x+5)/7[/tex]
Let
[tex]y=f(x)[/tex]
[tex]y= (3x+5)/7[/tex]
step 1
Exchange the variables x for y and y for x
[tex]x= (3y+5)/7[/tex]
step 2
Isolate the variable y
[tex]7x= (3y+5)[/tex]
[tex]3y=7x-5[/tex]
[tex]y=(7x-5)/3[/tex]
Let
[tex]f^{-1}(x)=y[/tex]
[tex]f^{-1}(x)=(7x-5)/3[/tex]